Pancasila Sebagai Kekuatan Moral Bangsa Di Tengah Tantangan Era Society 5.0 - Zahrani Salwa Azizah; Silmi Aulia Sholeh (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Technological developments in the era of Society 5.0 have had a major impact on various aspects of Indonesian society, both positive and negative. The combination of the physical and virtual worlds presents various moral challenges, such as the spread of false information, misuse of technology, and a decline in the frequency of social interaction. Pancasila, as the ideological foundation and worldview of the nation, plays a very important role in protecting the character, morals, and direction of the country's development so that it remains focused on human values. This article aims to assess the challenges faced by the Indonesian people in the era of Society 5.0 and identify the importance of Pancasila values as moral guidelines that can help in facing modern technological changes. The method used is a literature study by collecting various academic sources related to Pancasila and digital ethics issues. The results show that Pancasila can serve as the basis for digital ethics, character building, and a foundation for policies to maintain unity and social justice in the context of Society 5.0. Thus, Pancasila is still relevant as the moral force of the nation in facing the challenges of current technological changes. Keywords: Pancasila, Moral Force, Society 5.0, Digital Ethics, National Character